Penentuan Kelayakan Survei Kredit Calon Nasabah Menggunakan Metode Topsis Berbasis Web - Mochzen Gito Resmi; Muhamad Rafi Muttaqin (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
Debtor eligibility assessment must be examined carefully and carefully based on the criteria of the company, so that it takes a long time for the selection of suitable debtor candidates. Decision support system is part of the information system in overcoming problems for taking a decision that helps or provides alternatives in determining the eligibility of prospective debtors at PT. WOM FINANCE Purwakarta. With the TOPSIS method and the waterfall development method, where the results of prospective debtors are ranked based on predetermined administrative criteria. Debtor candidates who have the highest rank have the right to be surveyed first. implementation of the TOPSIS method on the system plays a major role on the effectiveness and efficiency of the company's services to consumers compared to before the system was implemented. With the implementation of the SPK system, it can help surveyors to make decision making decisions in the field easier. Keywords: Decision Support System (DSS), Credit, TOPSIS, Waterfall